Is that a fish in your ear? : translation and the meaning of everything - Bellos, David (Faber and Faber, 2011)
Funny and surprising on every page, Is That a Fish in Your Ear offers readers new insight into the mystery of how we come to know what someone else means whether we wish to understand Asteerix cartoons or a foreign head of state. Using translation as his lens, David Bellos shows how much we can learn about ourselves by exploring the ways we use translation, from the historical roots of written language to the stylistic choices of Ingmar Bergman, from the United Nations General Assembly to the significance of James Camerons Avatar. Is That a Fish in Your Ear ranges across human experience to describe why translation sits deep within us all, and why we need it in so many situations, from the spread of religion to our appreciation of literature; indeed, Bellos claims that all writers are by definition translators. Written with joie de vivre, reveling both in misunderstanding and communication, littered with wonderful asides, it promises any reader new eyes through which to understand the world. --amazon.com